1997
DOI: 10.1002/(sici)1097-4644(1997)28/29+<148::aid-jcb18>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer chemoprevention: Clinical development of aspirin as a chemopreventive agent

Abstract: We have studied aspirin as a potential chemopreventive for colorectal cancer, completing Phase I studies on aspirin pharmacology and potential biomarker assays (prostaglandins, PGE 2 and PGF 2␣ and cyclooxygenase modulation) in normal human subjects. These studies have determined the optimal dose of aspirin for future Phase IIa and IIb chemopreventive trials in high-risk cohorts of patients for colon cancer. Aspirin's effects on rectal prostaglandins are prolonged, detectable even after aspirin and its metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Several epidemiologic studies have shown that prolonged use of aspirin is associated with a significant reduction in the risk of developing and/or dying from cancer of the colon (1)(2)(3). Other nonsteroidal anti-inflammatory drugs (NSAIDs), have also been reported to cause a reduction in size and number of adenomas in familial adenomatous polyposis patients (4 -6).…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiologic studies have shown that prolonged use of aspirin is associated with a significant reduction in the risk of developing and/or dying from cancer of the colon (1)(2)(3). Other nonsteroidal anti-inflammatory drugs (NSAIDs), have also been reported to cause a reduction in size and number of adenomas in familial adenomatous polyposis patients (4 -6).…”
Section: Introductionmentioning
confidence: 99%
“…have shown promise in the prevention of colon cancer are aspirin and related nonsteroidal antiinflammatory drugs (NSAIDs) (2)(3)(4)(5)(6). .…”
mentioning
confidence: 99%
“…NSAIDs have inhibited the growth of colorectal cancer cells in vitro (7)(8)(9)(10)(11) , inhibited tumor formation in the colons of carcinogen treated rodents (12)(13)(14), and reduced adenoma counts in humans with familial adenomatous polyposis (15)(16)(17)(18). The most compelling evidence that NSAIDs prevent colon cancer comes from epidemiological data indicating that people who regularly take NSAIDs have a 40-50% reduced risk of dying from this disease compared with matched controls (2,17,19). However, the detrimental side effects of NSAIDs limit their potential as chemopreventative agents (20).…”
mentioning
confidence: 99%
“…2) Thus, interference with cell proliferation might prevent metastasis formation. Nonsteroidal anti-inflammatory drugs (NSAIDs) such as aspirin (ASP) and indomethacin (IM) are well-known as potential chemopreventive agents through their modulation of levels of prostaglandins, PGE2 and PGF2α, and cyclooxygenase (COX) in the colon, [3][4][5] and also other organs. [6][7][8][9] In order to evaluate the anti-metastatic potential of NSAIDs, two typical examples, ASP and IM were examined here using our in vivo lung metastasis model.…”
mentioning
confidence: 99%